Ending rheumatic heart disease in Australia: the evidence for a new approach. (15th November 2020) - Wyber, Rosemary; Noonan, Katharine; Halkon, Catherine; Enkel, Stephanie; Cannon, Jeffrey; Haynes, Emma; Mitchell, Alice G; Bessarab, Dawn C; Katzenellenbogen, Judith M; Bond‐Smith, Daniela; Seth, Rebecca; D'Antoine, Heather; et al.
Summary: ■ The RHD Endgame Strategy: the blueprint to eliminate rheumatic heart disease in Australia by 2031 (the Endgame Strategy) is the blueprint to eliminate rheumatic heart disease (RHD) in Australia by 2031. Aboriginal and Torres Strait Islander people live with one of the highest per capita burdens of RHD in the world. ■ The Endgame Strategy synthesises information compiled across the 5‐year lifespan of the End Rheumatic Heart Disease Centre of Research Excellence (END RHD CRE). Data and results from priority research projects across several disciplines of research complemented literature reviews, systematic reviews and narrative reviews. Further, the experiences of those working in acute rheumatic fever (ARF) and RHD control and those living with RHD to provide the technical evidence for eliminating RHD in Australia were included. ■ The lived experience of RHD is a critical factor in health outcomes. All future strategies to address ARF and RHD must prioritise Aboriginal and Torres Strait Islander people's knowledge, perspectives and experiences and develop co‐designed approaches to RHD elimination. The environmental, economic, social and political context of RHD in Australia is inexorably linked to ending the disease. ■ Statistical modelling undertaken in 2019 looked at the economic and health impacts of implementing an indicative strategy to eliminate RHD by 2031. Beginning in 2019, the strategy would include: reducing household crowding, improving hygiene infrastructure, strengthening primary health care and improving secondary prophylaxis. It was estimated that the strategy would prevent 663 deaths and save the health care system $188 million. ■ The Endgame Strategy provides the evidence for a new approach to RHD elimination. It proposes an implementation framework of five priority action areas. These focus on strategies to prevent new cases of ARF and RHD early in the causal pathway from Streptococcus pyogenes exposure to ARF, and strategies that address the critical systems and structural changes needed to support a comprehensive RHD elimination strategy.